2012
DOI: 10.1002/j.1556-6676.2012.00048.x
|View full text |Cite
|
Sign up to set email alerts
|

Counseling and Mental Health Care in Palestine

Abstract: The authors provide a brief overview of counseling and mental health care in Palestine, including their history and a summary of their current status. Finally, a discussion is presented of future trends in the development of the profession with regard to recent changes in the region.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…This violence and intentional de-development [44] of infrastructure and essential services has been shown to severely impact on mental health in the Palestinian population [49][50][51][52]. In response, the Palestinian Authority established 16 Community Mental Health Centres [53,54].…”
Section: Occupied Palestinian Territorymentioning
confidence: 99%
“…This violence and intentional de-development [44] of infrastructure and essential services has been shown to severely impact on mental health in the Palestinian population [49][50][51][52]. In response, the Palestinian Authority established 16 Community Mental Health Centres [53,54].…”
Section: Occupied Palestinian Territorymentioning
confidence: 99%
“…In Islam, the community (umma) is considered one body. Researchers have suggested that less individualistic models aimed at the community are needed in places like Palestine (Makkawi, 2015;Shawahin & Çiftçi, 2012). When one part of the umma hurts, all of its other parts hurt as well.…”
Section: Directive Approaches Cultural Humility and Collectivistic mentioning
confidence: 99%